Penerapan Good Manufacturing Practice (GMP) Dan Analisis Kelayakan Usaha Pada Industri Kerupuk Jangek Skala Rumah Tangga - Hamizar Sayuti; Yudian Syahputra; Hesti Nur’aini; Lina Widawati; Diah Azhari (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Jangek cracker products are animal-derived foods, which have a high risk of contamination, so the implementation of GMP is absolutely necessary to ensure product safety and quality. Gap analysis was conducted by comparing practices in business units with the standards of the Indonesian Ministry of Industry Number 75 of 2010, while financial feasibility was measured using cost analysis, income, and Revenue/Cost Ratio (R/C Ratio). The production process of Jangek crackers in the Etek Jas home industry is still traditional and intensive, involving critical stages such as liming and open-air drying for 2–3 days. Significant gaps were found in the packaging stage, which was not equipped with informative labels (brand, composition, production date), as well as the vulnerability of post-process contamination during the drying stage. The overall implementation of GMP was categorized as Good with an average percentage of 84%. The Building Aspect had the highest score (93%). However, there are critical gaps (Major Non-Conformities) in the Sanitation Facilities (81%) and Employees (83%) aspects, which focus on a simple liquid waste disposal system and inconsistent use of complete work attributes (PPE) by employees. This business is stated to be very efficient, profitable, and feasible to be developed. This is evidenced by the R/C Ratio value of 1.29, which indicates that every Rp 1.00 of costs generates Rp 1.29 in revenue. The cost structure is dominated by Variable Costs (99.63% of TC), with cowhide as the largest cost component (79.55% of TVC).